Peningkatan Kemampuan Komunikasi Matematis Menggunakan Model Pembelajaran Problem Based Learning dengan Konteks Kemaritiman: Materi Statistika - Putri Sekar Sari; Metta Liana; Aang Yudho Prastowo (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
The aim of this research was to examine how students' mathematical communication improved when the problem-based learning model with maritime context was utilized and to determine whether this improvement outweighed any benefits of using the conventional model. Pretest-posttest control group design was the study strategy employed. Cluster sampling was used as the sampling method. Class VIII D comprised the control group, whereas Class VIII F served as the experimental group. Tests and non-tests were used as data collection methods. The precondition test, hypothesis testing, and N-Gain test are examples of data analysis approaches. In both the paired and unpaired T-tests, the study's findings yielded a Sig. (2-tailed) of 0.001.  Due to the one-party nature of the test (right-party test), the P-value  was discovered, leading to the acceptance of  and the rejection of . Thus, it can be said that students who use a problem-based learning model with a maritime context for their education have much improved mathematical communication skills and that there are differences in the improvement of mathematical communication skills between students in the control class and the experimental class.